Capital Resalability, Productivity Dispersion, and Market Structure - Balasubramanian, Natarajan; Sivadasan, Jagadeesh (The Review of Economics and Statistics, 2009)
We propose an industry-level index of capital resalability—the share of used capital in aggregate industry capital expenditure—that relates (inversely) to sunkenness of investments. Using data from U.S. manufacturing, we then test the effect of capital resalability on industry productivity dispersion, mean productivity, and industry concentration. As predicted by standard models of industry equilibrium with heterogeneous firms, we find that increases in capital resalability are associated with a reduction in productivity dispersion, and an increase in the mean and median of the productivity distribution. Furthermore, we find that capital resalability is negatively correlated with industry concentration.